Legal Education to Prevent Juvenile Delinquency at Muhammadiyah Junior High School 1, Sleman - Dakum, Dakum; Syafingi, Habib Muhsin; Hidayah, Ngirfah; Qotrunada, Amelia; Efendi, Rahmadhani Widi (Borobudur Journal on Legal Services, 2025)
The phenomenon of juvenile delinquency is increasingly alarming, as reflected in various forms of misconduct ranging from bullying and drug abuse to street crimes. This condition is often caused by limited legal literacy and adolescents’ lack of awareness of the legal consequences of their actions. SMP Muhammadiyah 1 Sleman, as an educational institution, plays a vital role in protecting students from such deviant behavior. The purpose of this community service activity was to improve students’ legal understanding in order to foster law-abiding behavior. The implementation method employed interactive legal counseling, which included lectures, question-and-answer discussions, and case simulations. The effectiveness of the activity was evaluated through the distribution of pre-tests before the material was delivered and post-tests after the activity was completed to measure the increase in participants’ knowledge. The target of this activity consisted of 70 students of SMP Muhammadiyah 1 Sleman representing each class. The results of the community service activity indicated a significant improvement in the partners’ understanding. Based on the evaluation, there was an 80% increase in the average score of students’ knowledge regarding types of juvenile criminal acts and their legal sanctions compared to before the counseling. The students also showed high enthusiasm and were able to identify actions that violate the law during the discussion sessions. The implications of this activity include the formation of legally aware agents within the school environment, which is expected to minimize the potential for legal violations and create a conducive, safe, and disciplined school environment.